Analisis Pembelajaran Daring dan Kesulitan Belajar di Masa Pandemi Covid 19 pada Mata Pelajaran Geografi Kelas X Di SMA Negeri 2 Balige Tahun Pelajaran 2021/2022 Semester Genap - Emma Rouli Pasaribu; Ulung Napitu; Mariah S.M. Purba (Departement of Mathematics Education, 2023)
This study aims to Analyze Online Learning And Learning Difficulties In The Covid-19 Pandemic Period In Grade X Geography Subject At Sma Negeri 2 Balige Academic Year 2021/2022 Even Semester. Data collection techniques used by researchers are library research and interviews. Data analysis techniques in this study used qualitative analysis techniques and conclusions were drawn after all the answers to the questions were transcribed and tabulated. The results showed that the learning difficulties of students towards online learning at SMA Negeri 2 Balige, Toba Regency, namely that some students did not have the facilities or cellphones to access online learning due to the inability of the students, the internet network which was sometimes less stable because they were in areas that did not support the network, it is difficult to focus on online learning because students do not really understand the material taught by the teacher, limited data credit or internet city, and some students do not understand about online learning applications.